Malignant Mesothelioma Presenting as a Gradually Enlarging Pneumothorax - Ashish Prasad; Diana Olsen; P. S. Sriram (Case Reports in Pulmonology)
Malignant mesothelioma is an extremely aggressive tumor arising from the pleura with median survival of approximately 9–12 months. It can rarely present as a spontaneous pneumothorax. Less than 35 cases of malignant mesothelioma presenting as spontaneous pneumothorax have been reported in the literature. Pathology may show florid mesothelial hyperplasia. We herein report a case of mesothelioma presenting as a pneumothorax that gradually enlarged over a one-year period and also review the relevant literature.